1973
DOI: 10.1111/j.1365-2818.1973.tb03808.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of the internal cellular structure of plants

Abstract: SUMMARY A technique is described in which the scanning electron microscope (SEM) has been used to study the internal cellular organization of the plant organs and the interaction of the plant with the environment. Transverse surfaces were revealed by fracturing quick frozen specimens and freeze‐drying the fragments. The greater depth of focus of the SEM compared with the optical microscope enabled the production of clear, realistic micrographs with a three‐dimensional appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Both of these freezing methods have the advantage that frozen tissue can be fractured or cut to leave clean sections through the tissue enabling internal cellular structure to be studied at the same time as the topographical features. We have found that freeze fracturing tissue prior to freeze drying has enabled us to look at internal plant structure in a new way by utilizing the large depth of focus of the Stereoscan (Bole & Parsons, 1973). Some temperature controlled specimen stages have a knife incorporated with them to enable successive layers of frozen tissue to be removed (Hasegawa & Yotsumoto, 1972).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Both of these freezing methods have the advantage that frozen tissue can be fractured or cut to leave clean sections through the tissue enabling internal cellular structure to be studied at the same time as the topographical features. We have found that freeze fracturing tissue prior to freeze drying has enabled us to look at internal plant structure in a new way by utilizing the large depth of focus of the Stereoscan (Bole & Parsons, 1973). Some temperature controlled specimen stages have a knife incorporated with them to enable successive layers of frozen tissue to be removed (Hasegawa & Yotsumoto, 1972).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…At first we examined internal structures by gluing specimens to the disc, freezing, then fracturing whilst still under LN, and examining still frozen. A procedure similar to those described by Haggis (1972) and Bole & Parsons (1973) except that we did not freeze-dry the specimens. Unfortunately specimens tended to lift off the disc whilst they were being fractured and were very difficult to fix again.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Previous techniques for fracturing frozen, biological specimens (e.g. Haggis, 1972;Bole & Parsons, 1973) all involve freeze-drying or the use of a cold stage. Hasegawa & Yotsumoto (1973) described a cold stage for a JSM-2 SEM in which a knife is mounted in an antechamber so that specimens may be fractured and if required successive layers of tissue removed while the specimen is kept frozen and under vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…A chamber has been developed that attaches to the SEM and that is used for fracturing and coating biological samples (Pawley and Norton, 1978). Such a device may be particularly useful for examining internal cellular structures of fungi (Laane, 1972(Laane, , 1974Bole and Parsons, 1973;Kirschner and Rusli, 1976). Application of X-ray microanalysis to fungal taxonomy is in the pioneering stage and may be another useful technique for future investigations (Ernst and Winkelma, 1977;Meisch et al, 1977;Thibaut et al, 1977;Doerge et al, 1978;Urbanus^a/., 1978).…”
Section: Introductionmentioning
confidence: 99%